2020
DOI: 10.1021/acsomega.0c00737
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects of Cellulose on Hydrolysis and Carbonization Behavior during Hydrothermal Treatment

Abstract: This study aims to investigate how the morphology of cellulose influences the hydrolysis and carbonization during hydrothermal treatment at temperatures between 180 and 240 °C. The morphology of cellulose, especially different crystallinities and degrees of polymerization, is represented by microcrystalline cellulose and α-cellulose. Kinetic analysis is considered a tool to allow the determination of the mechanisms of the two types of cellulose during the hydrothermal process. A kinetic model, in which cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 83 publications
4
52
0
Order By: Relevance
“…Differences between the raw sugar beets and the spent sugar beets may be caused by a partial hydrolysis of the amorphous part of cellulose during sugar extraction, while the crystalline structure remains mostly unaffected in the SPB. This agrees with previous studies, which showed that the amorphous structure of the cellulose tends to be hydrolyzed faster than the crystalline structure [ 5 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Differences between the raw sugar beets and the spent sugar beets may be caused by a partial hydrolysis of the amorphous part of cellulose during sugar extraction, while the crystalline structure remains mostly unaffected in the SPB. This agrees with previous studies, which showed that the amorphous structure of the cellulose tends to be hydrolyzed faster than the crystalline structure [ 5 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 93%
“…Thermochemical conversion of biomass is considered as one of the pathways for the production of renewable energy and valuable chemicals or materials. The study of different thermochemical processes such as pyrolysis, gasification, combustion and hydrothermal carbonization (HTC) are well-illustrated in previous studies with model compounds (i.e., microcrystalline cellulose and glucose) for the production of different products [ 3 , 4 , 5 ]. On the other hand, the wish to use biomass in the frame of biorefinery still necessitates research to improve the processes and implement different kinds of biomasses.…”
Section: Introductionmentioning
confidence: 99%
“…The datasets encompass a wide range of operational conditions and serve as a stress-test for assessing the routines' reliability. Substrates are representative of herbaceous biomass [miscanthus (Smith and Ross, 2019)], model carbohydrates [cellulose (Paksung et al, 2020)], lignocellulosic materials (fir) and agro-food industry scraps (potato starch). Temperature ranges from 200 to 250 • C, reaction duration from 2 to 24 h, the solid-liquid ratio from 1:3.5 to 1:14.…”
Section: Programsmentioning
confidence: 99%
“…The remaining schemes are worth considering as tentative, more detailed descriptions of the HTC reactions. The literature remarks on the solid-phase autocatalytic behavior of HTC (Brown, 1997;Paksung et al, 2020), and the first reaction of schemes 2, 3, and 6 accounts for this. For activating the process, a certain amount of HC1 should be present as the reactions start (time zero, reactor heated up to the setpoint temperature).…”
Section: Scheme Network Propensity Functionsmentioning
confidence: 99%
See 1 more Smart Citation